The importance of financial aids for postgraduate students and alternatives for developing them from the perspective of students and employees at Taibah University - Al-Harbi, Najwa Obaid; Al-Shamy, AlSaeed Saad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the importance of financial aids for postgraduate students and the alternatives for developing them from the perspective of students and employees at Taibah University. To achieve this goal, the researcher adopted the descriptive analytical approach. The data of the study were collected through a questionnaire applied to a random sample of (322) postgraduate students for the year 1442 AH / 2021, in addition to a structured interview with a Purposive sample of (5) of those in charge of postgraduate studies at Taibah University. The main findings of the study showed a strong agreement of the sample on the domains of the questionnaire, with a total average of (4.29 out of 5). The domain of the importance of providing financial aid programs got an overall average (4.21 out of 5), whereas the domain of alternatives for providing financial aid programs to postgraduate students got an overall average (4.37 out of 5), both of which are graded high (very important). At the level of phrases, their arithmetic averages ranged between 3.88 to 4.57, and these averages fall into the fourth and fifth categories of the 5- point scale that indicate to (agree) and (strongly agree). It was also found that the most important reasons for providing financial aid programs are: assisting unemployed students, low- income students, students with disability, academically outstanding students, children of martyrs and the students of social security. The most important alternatives for providing financial aid programs to students are in the form of student employment (part- time jobs) at university or other sectors, or a loan from the student fund, or an interest- free loan through partnership with banks or other companies. Based on the results, the researcher presented a proposed perspective for financial aid programs for postgraduate students at Taibah University according to the results of the study, in addition to recommendations to ensure the success of the proposed perspective and suggestions for future studies on the subject.
Keywords: financial aids; perspectives; postgraduate students; Taibah University